Guidelines Towards the Facilitation of Interactive Online Learning Programmes in Higher Education - Mbati, Lydia; Minnaar, Ansie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The creation of online platforms that establish new learning environments has led to the proliferation of institutions offering online learning programmes. However, the use of technologies for teaching and learning requires sound content specialization, as well as grounding in pedagogy. While gains made by constructivism and observational learning are well documented, research addressing online practices that best encourage constructivist and observational learning in Open and Distance Learning (ODL) contexts is limited. Using a phenomenological methodological approach, this research explored the lived experiences of online learning programme facilitators at an Open and Distance Learning higher education institution. The findings of this research study revealed that facilitators did not use constructivist and observational learning pedagogies to a large extent in their interaction with students. It is concluded that during the curriculum planning phase, facilitators should decide on methods and media to arouse the students’ attention and stimulating constructivist and observational learning amongst students during online courses. This also implies a more reasonable facilitator-student ratio because large numbers of students per facilitator proves not feasible in online learning. The paper concludes by providing guidelines for the facilitation of interactive online learning programmes.